Assessment of Buccal and Palatal Alveolar Bone Thickness in Maxillary Anterior Teeth on Cone Beam Computed Tomography - Mohammad Sadegh Shiranizadeh; Azadeh Torkzadeh; Afshin Yadegari-Naein; Seyed Sasan Aryanezhad (Isfahan University of Medical Sciences, 2021)
Evaluating the dimensions of buccal and palatal alveolar bone in the anterior maxillary teeth is very important in patients who are candidates for immediate implant replacement. The aim of this study was Assessment of buccal and palatal alveolar bone thickness in maxillary anterior teeth on cone beam computed tomography (CBCT).Materials & Methods:In this descriptive-analytical study, 78 CBCT images of patients referred to Radiology Department of Khorasgan Dental Faculty were evaluated. The collected data included the measurement of the bone thickness of the alveolar buccal and palatal anterior maxillary teeth at three locations of the crest, the middle region of the root and apex with the Sidexis software. Then, the measurements were compared between males and females. The data were analyzed by T-test statistical methods.Results:The mean thickness of the buccal alveolar bone in the crest region and the middle region of the central, lateral and canine teeth was less than 1 mm. The mean thickness of the buccal alveolar bone at the apex site of the central, lateral and canine teeth was more than one mm. The mean thickness of the palatal alveolar bone in the crest region of the central, lateral and canine teeth was less than one millimeters. The mean thickness of the palatal alveolar bone in the middle region of the root and apex was more than one mm. There was no statistically significant difference between the sex and thickness of the buccal alveolar bone, except at the apex of the central and lateral teeth (p value > 0.05). Between sex and thickness of palatal alveolar bone, in the crest of lateral and canine teeth and in the middle root and apex area of all three central, lateral and canine teeth in men were significantly more than women (p value < 0.05).Conclusion:The buccal alveolar bone was present in most of the points examined at the crest and mid-root site, and the palatal alveolar bone was at the crest site at most checked points with a thickness of less than 1 mm.